Analyzing the Effectiveness of Electric Vehicles in Indonesia: A Malthusian Approach to Resource and Emission Management - Michael Adrian Widyawan (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
This research will explore some of the best solutions to global warming through the perspective of electric vehicles. The methodology will be a mix of survey methods, case studies comparing Indonesia and Singapore, and interviews with experts to understand public perception, analyze real examples, and garner expert views. The findings indicate significant barriers towards the adoption of EVs in Indonesia due to inadequate charging infrastructure, high costs, and range anxiety; Singapore, through urban challenges coupled with government policies, has a high rate of adoption. It is clear that technological advancements in EVs themselves, charging infrastructure, and policy frameworks will have to be in place for greater adoptions to be encouraged. Key recommendations include cultivating natural demand through consumer awareness campaigns, government incentives, and integration of renewable energy sources into charging infrastructure. Though there are limitations to this study, the findings provide valuable additions to the ongoing discourse on sustainable transportation and climate change mitigation in developing countries.